PERANCANGAN BENDUNG GERAK KARANGTALUN DI KABUPATEN KULON PROGO, YOGYAKARTA - Garyas Praja Siswadi; Saktyianto Ajinugroho; Suseno Darsono; Sugiyanto Sugiyanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
In addition to the construction of an alternative form of water reservoirs, to tackle the problem at the Weirs Karangtalun can also be by way of construction of the barrage. The reason for the need for the construction of the dam movement emerged based on the survey results, which show that Karangtalun weir downstream conditions are now damaged due deggredasi riverbed downstream. Weir crest had already suffered some damage due to collision damage to the stone. It is feared that one day the dam will collapse.Barrage to capture the motion of the water to drain Progo river can be more time in the count because of the barrage that comes w ith taking the doors and door rinse. raw water needs in the catchemet area Progo 2 of irrigation kalibawang and mataram, flood discharge plan is designed with 100-year return period of 1157 m3/sec.Barrage height of 10 m. Weir is equipped with radial main door, stilling basin using the threshold type width of 35 m. Construction of barrage to cost about 222 billion and a plan of implementation 40 weeks.